Increased risk of pertussis in adult patients with mannose‐binding lectin deficiency. Issue 4 (13th September 2012) - Gröndahl‐Yli‐Hannuksela, Kirsi; Viander, Markku; Mertsola, Jussi; He, Qiushui
<x xml:space="preserve">Abstract</x> Mannose‐binding lectin (MBL) is an important molecule of the innate immunity. The low level of MBL in the serum is associated with increased susceptibility to respiratory infections. In this study, MBL concentrations were determined from the sera of 125 Finnish pertussis patients and from 430 control subjects. Severe MBL deficiency (<50 ng/mL) was found more often in the patients than in the controls (11.2% vs 5.8%, p = 0.038). Moreover, the deficiency was detected more frequently in the adult patients than in the controls [20.4% vs 8.6%, p = 0.021; odds ratio 2.7 (95% confidence interval 1.1–6.5)]. Our findings suggest, for the first time, that MBL deficiency predisposes to pertussis infection, at least in adults.